Ações ambientais em meios de hospedagem da Região Uva e Vinho da serra gaúcha - RS - Silva, Roberto do Nascimento e (My University, 2014)
The following paper seeks to pinpoint the factors which interfere with the adoption of environmental actions within the hotel network in the Region of Vineyards and Wineries, RS, Brazil, as well as to evaluate the relations among them.In order to collect the data we have resorted to structured interviews,based on an inquiry with 16 questions encompassing issues such as electricity, water (supply), solid residues, suppliers, the sensitizing of supporters and environmental adequacy. We also used the classification of the Brazilian Institute of Tourism – EMBRATUR to guide our interviews. A total of 40 people were interviewed, i.e., hotel managers.The results have shown in which ways those hotels adopt (or not) environmental actions and which factors were determining for the adoption of such.We were able to verify the meaningfulness of the adoption by hotels of 13 environmental actions from the EMBRATUR classifying matrix.The results unveil good practices of energy management and the sorting of residues.Some rare practices still linger concerning water use, storage of hazardous materials, choice of suppliers, environmental adequacy and education.The factors which determine the adoption of environmentally friendly actions are closely related to the information regarding the environmental phenomenon, sensitivity towards environmental practices, formation (education) of hotel managers, size of enterprises, kinds of management, energy costs, water supplying costs, environmental programs, negligence to adopt environmental actions, lack of environmental policies,lack of responsability by hotel businesses and gaps in architectural projects. In short, for environmental issues in hotel management to become a reality, there must be greater sensitizing of their managers, greater diffusion of the importance of developing environmental practices, greater surveillance by environmental authorities and deeper analysis of environmental questions throughout hotel and tourism courses´ curricula.
Este estudo tem por objetivo determinar fatores que interferem na adoção de ações ambientais nos meios de hospedagem da Região Uva e Vinho, como também avaliar as relações que se estabelecem entre os mesmos. A técnica empregada para a coleta de dados nesta pesquisa foi a entrevista estruturada, embasada num roteiro de 16 questões contendo informações referentes à energia, água, a resíduos sólidos, fornecedores, sensibilização dos colaboradores e a adequação ambiental. Para a construção do roteiro de entrevistas, foi utilizada a matriz de classificação do Instituto Brasileiro de Turismo EMBRATUR como ferramenta de apoio a este estudo. Foram feitas entrevistas com 40 sujeitos (gestores de meios de hospedagem). Os resultados demonstraram como os meios de hospedagem adotam ou não ações ambientais e os fatores determinantes para a adoção dessas ações. Foi possível verificar ainda a importância da adoção das 13 ações ambientais da Matriz de Classificação da Embratur para os empreendimentos hoteleiros. Os resultados obtidos apontam para boas práticas para o gerenciamento de energia e separação de resíduos. Práticas ainda escassas estão relacionadas ao uso da água, ao armazenamento de resíduos perigosos, escolha de fornecedores, adequação ambiental e educação ambiental. Os fatores que determinam a adoção de ações ambientais estão relacionados à informação sobre o fenômeno ambiental, sensibilidade em relação às práticas ambientais, formação dos gestores hoteleiros, porte dos empreendimentos, tipo de administração, custo de energia, custo de água, programas ambientais, descaso com a adoção de ações ambientais, ausência de política ambiental, ausência de responsabilidade da empresa e lacunas nos projetos arquitetônicos. Em síntese, para que ações ambientais na hotelaria sejam mais freqüentes, deve haver uma maior sensibilização dos gestores de meios de hospedagem, uma maior divulgação sobre a importância do desenvolvimento de práticas ambientais, uma maior fiscalização por parte dos órgãos ambientais e uma maior análise das questões ambientais nos cursos de hotelaria e turismo.
Keywords: Turismo; Turismo; Planejamento e gestão do turismo; Hospitalidade; Ações ambientais em meios de hospedagem; Região Uva e Vinho, RS; Hotelaria; Serra gaúcha, RS; Desenvolvimento sustentável; Tourism; Tourism planning and management; Hospitality; Environmental actions by hotel businessess; The Region of Vineyards and Wineries, RS, Brazil